Converging formalisations of communicational spaces. (2015) - Ahamer, Gilbert
Based on statistical mechanics and on communication and its probabilities, this article deals with the concept of communicational spaces and tries to renew, clarify and formalise it from a physical and mathematical standpoint. Starting out from the likelihood of communication, distance in space is defined according to the number of options to communicate. A century ago, the formalisms of statistical thermodynamics were developed mainly by Ludwig Boltzmann to deal with a large number of states in a state space. Such formalism is applied to the large number of options to communicate. In this tradition, a definition of distance in space is attempted. Each form of communication is thought to constitute its own type of space. More generally, space is seen as an opportunity for processes; and time is seen as a substrate to enact processes. In a less formulaic chapter, a definition of space is explored on the basis of principal options to interact. The social and practical implications of such conception are explored. In conclusion, the deep meaning of space is understood in the sense that space separates possibilities for communication.